Design of the Monthly Educational Development Contribution Payment Application for Santri at the Syekh Hamzah Al Fansury Islamic Boarding School in Subulussalam City - Nurhasanah, Putteri; Ahmad, Adi; Maulana, Riyan (STMIK Indonesia Banda Aceh, 2025)
Pondok Pesantren Sheikh Hamzah Al Fansury in Subulussalam City prioritizes optimal educational services, including in the aspect of paying the Education Development Contribution (SPP) for around 300 students. The growing number of new students requires the development of a more efficient and detailed payment system. Currently, the payment process still uses manual methods that tend to be ineffective. The recording of SPP payment transactions is done through cards which are then manually recapitulated into the ledger by the treasurer. This condition creates a risk of errors and data loss, especially if the payment card is lost. With the SPP payment application, it is expected that efficiency and data security will increase. SPP payments will be recorded more accurately and stored securely in the database. The use of a computerized information system is also expected to minimize errors and facilitate access to payment data, especially in making financial reports. This research is an effort to develop a web-based SPP payment application for the Sheikh Hamzah Al Fansury Islamic Boarding School. A qualitative approach was used to understand the needs of potential users, while the waterfall software development method was chosen to ensure a structured application design process. The results showed that this application was successful in simplifying the payment process, printing receipts, and presenting reports accurately. It is hoped that this application can be an effective solution to improve the quality of tuition payment services for students at the Sheikh Hamzah Al Fansury Islamic Boarding School.